2020
DOI: 10.1016/j.molbiopara.2020.111301
|View full text |Cite
|
Sign up to set email alerts
|

Direct and high-throughput assays for human cell killing through trogocytosis by Entamoeba histolytica

Abstract: Entamoeba histolytica is a microbial eukaryote and causative agent of the diarrheal disease amoebiasis. Pathogenesis is associated with profound damage to human tissues, and treatment options are limited. We discovered that amoebae attack and kill human cells through a cell-nibbling process that we named trogocytosis (trogo-: nibble). Trogocytosis is likely to underlie tissue damage during infection and it represents a potential target for therapeutic intervention, although the mechanism is still unknown. Assa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…To perform the capturing of the prey, in general, trophozoites require to adhere to the target. The virulent strains of E. histolytica display a high rate of pinocytosis (micropinocytosis and macropinocytosis) and endocytosis (trogocytosis and phagocytosis) (Rodrıǵuez and Orozco, 1986;Laughlin et al, 2004;Bettadapur and Ralston, 2020). Pinocytosis is the process by which the trophozoites absorb extracellular fluids and compounds (Laughlin et al, 2004), while in endocytosis, the cells capture macromolecules, cell surface components and even whole cells that include red blood cells (RBCs), live and apoptotic mammalian cells, and bacteria (Labruyère and Guilleń, 2006).…”
Section: Target Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…To perform the capturing of the prey, in general, trophozoites require to adhere to the target. The virulent strains of E. histolytica display a high rate of pinocytosis (micropinocytosis and macropinocytosis) and endocytosis (trogocytosis and phagocytosis) (Rodrıǵuez and Orozco, 1986;Laughlin et al, 2004;Bettadapur and Ralston, 2020). Pinocytosis is the process by which the trophozoites absorb extracellular fluids and compounds (Laughlin et al, 2004), while in endocytosis, the cells capture macromolecules, cell surface components and even whole cells that include red blood cells (RBCs), live and apoptotic mammalian cells, and bacteria (Labruyère and Guilleń, 2006).…”
Section: Target Recognitionmentioning
confidence: 99%
“…Endocytic processes include phagocytosis, that refers to live whole, damaged or dead cells engulfment; and trogocytosis, where trophozoites ingest part of the living cells ( Ralston et al., 2014 ; Bettadapur and Ralston, 2020 ; Nakada-Tsukui and Nozaki, 2021 ). The PM invagination and the formation of vesicles and vacuoles required for these processes, imply the renewal of the PM every 30 min ( Doherty and McMahon, 2009 ).…”
Section: Participation Of Escrt In Recognition and Capturing Of The P...mentioning
confidence: 99%
“…Furthermore, Somlata et al [ 25 ] documented that AGC family kinase 1 was specifically involved in trogocytosis of living human cells but not participate in phagocytosis of dead cells by Eh. Recently, Bettadapur et al [ 26 ] by using direct and high-throughput assay demonstrated that inhibition of human cell actin or amoeba surface Gal/GalNAc lectin could inhibit amoebic trogocytosis.…”
Section: Trogocytosis-associated Cytopathic Effects Immune Evasiomentioning
confidence: 99%
“…0.5 ml of cells were seeded (at ∼5 × 10 5 cells/ml) into a 24-well plate preloaded with 0.5 ml fresh M7 medium with inhibitors or controls for final (1×) concentrations as follows: 5 µM LatB, 20 µM cytochalasin D, 140 nM phalloidin, 2 µM jasplakinolide, 50 µM CK-666, 25 µM SMIFH2, 50 µM CK-689, 0.1% DMSO, and 0.09% ethanol. Concentrations were selected based on work in other systems (Bettadapur and Ralston, 2020;Fritz-Laylin et al, 2017b;Jahan and Yumura, 2017;Jasnin et al, 2016;Manich et al, 2018;Olins and Olins, 2004;Ralston et al, 2014;Spector et al, 1983;Velle and Campellone, 2018;Wang et al, 2014;Williams and Kay, 2018;Wilson et al, 2013) and/ or were tested at 10-fold dilutions within the range recommended in the company-supplied data sheets in preliminary experiments. From preliminary experiments, the lowest concentration that had an observable phenotype in live cells was chosen, or in the case of cytochalasin D, jasplakinolide, and phalloidin, the highest concentrations we tested were chosen, which still did not produce any obvious phenotypes.…”
Section: Cell Morphology Assays and Use Of Inhibitorsmentioning
confidence: 99%